Symposium 6: Design of a Networked Learning Master Environment for Professionals – using the approach of problem based learning to establish a community of practice - Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2010)
The paper is presenting the overall learning design of MIL (Master in ICT and Learning). The learning design is integrating the principles of: 1. Problem and project based learning 2. Networked learning / learning in communities of practice. The paper discusses how these principles interact productively in the design of a networked learning environment for professionals. The paper challenge the definition of networked learning focussing on connections. This definition has been important to throw light upon the importance of weak ties, and how much weak ties are used within networks. However in order to really use the potentials of the socio cultural understanding of learning as based in relationships and connections we need a stronger concept of networked learning as a socio-technical way of organising learning, which make learners interact, connect, engage, relate and collaborate on joint enterprises and activities, through both strong and weak ties, and to dynamically accumulate and rework concepts, artefacts and knowledge in a variety of forms and from a variety of sources. The MIL case based on problem and project based learning demonstrates how this understandings of networked learning can be organised for. MIL is based on a pragmatic concept of problem and project based learning adapted to the virtual conditions of networked learning. The MIL model incorporates a series of integrated didactical principles: problem formulation, enquiry of exemplary problems, participant control, joint projects, dialogues, interdisciplinary approaches, and action learning. The approach requires that students and teachers (facilitators, supervisors, lecturers, and professors) engage in a shared enterprise – a project - within the thematic framework of the semester. The study program is organised around two main activities: 1. course work in order to get insights of the core disciplines and to build up a shared repertoire and 2. project work, where the students engage in collaborative research projects – as a kind of shared enterprise. From a learning point of view the pedagogical principles of PBL facilitates as well the individual learner’s constructions of knowledge as well as the project group’s construction of shared understanding through negotiations, confrontations and identification. Further more previous research has shown, that PBL facilitates inter-dependencies among the busy professionals, which help them to prioritize the study of work and also to establish kinds of community of practice.